THE EFFECT OF ONLINE LEARNING SYSTEM DURING THE COVID-19 PANDEMIC ON STUDENTS' LEARNING MOTIVATION AND INTEREST IN LEARNING - gilang maulana jamaludin; dedika supriatna; ahmad zacky burhani (Universitas Islam Negeri (UIN) Mataram, 2020)
This research is motivated by a problem that shows the student motivation and interest in learning in Islamic religious education subjects at SMP Plus Hafadata Yusuf, Argapura District are generally still low, seen in students complaining about subject matter that is difficult to understand with photocopied presentation during the Covid-19 Pandemic, the school is not ready to implement an online learning system.This study aims to find out (i) to find out how the online learning system at SMP Plus Hafadata Yusuf (ii) to find out how the students 'learning motivation at SMP Plus Hafadata Yusuf (iii) to find out how the students' learning interest at SMP Plus Hafadata Yusuf (iv) To find out the effect of the Covid-19 Pandemic Online Learning System on Student Motivation and Learning Interest at SMP Plus Hafadata Yusuf. In general, this researcher is empirical by using quantitative research methods, this type of experimental research. The technique of collecting data by means of observation, interviews, questionnaires or questionnaires, and documentation. The influence of the online learning system during the Covid-19 Pandemic period on learning motivation and interest in learning in class VII Islamic religious education subjects at SMP Plus Hafadata Yusuf, the results (pretest) before the treatment (treatment) of the experimental group with an average value of learning motivation is 62 , 86 and interest in learning is 62.86, the control group with an average value of learning motivation is 61.47 and interest in learning is 59.33. While the results (posttest) after giving treatment (treatment) obtained an F value which assumes that the two variants are the same is 0.545 with a value of t = 9.464 with degrees of freedom (df) = n1 + n2 - 2 = (14 + 15-2 = 27). ? = 0.05 obtained Sig. 0,000. Because of Sig. 0,000 <0.05, thus H0 is rejected or in other words Ha is accepted. Obtained the F value which assumes that the two variants are the same is 3,428 with a value of t = 10,244 with degrees of freedom (df) = n1 + n2 - 2 = (14 + 15 - 2 = 27). ? = 0.05 obtained Sig. 0,000. Because of Sig. 0,000 <0.05 thus H0 is rejected or in other words Ha is accepted, meaning that there is a significant difference, this indicates that the use of online learning systems can affect student learning motivation and interest than those who do not use online learning.